2021
DOI: 10.3389/fphar.2021.669037
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Stromal Cell-Secretome Counteracts Profibrotic Signals From IPF Lung Matrices

Abstract: Introduction: Idiopathic pulmonary fibrosis (IPF) is a fibrotic lung disease characterized by excess deposition and altered structure of extracellular matrix (ECM) in the lungs. The fibrotic ECM is paramount in directing resident cells toward a profibrotic phenotype. Collagens, an important part of the fibrotic ECM, have been shown to be structurally different in IPF. To further understand the disease to develop better treatments, the signals from the ECM that drive fibrosis need to be identified. Adipose tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 57 publications
(68 reference statements)
1
2
0
Order By: Relevance
“…The application of adipose tissue-derived stromal cell conditioned medium (ASC-CM) in the ex vivo culture model resulted in less ECM deposition. 154 This research suggested that ASC-CM probably inhibit fibrotic ECM-induced profibrosis of fibroblast, and confirmed the efficiency of the ex vivo platform.…”
Section: Decellularized Fibrotic Lung Matrixsupporting
confidence: 66%
“…The application of adipose tissue-derived stromal cell conditioned medium (ASC-CM) in the ex vivo culture model resulted in less ECM deposition. 154 This research suggested that ASC-CM probably inhibit fibrotic ECM-induced profibrosis of fibroblast, and confirmed the efficiency of the ex vivo platform.…”
Section: Decellularized Fibrotic Lung Matrixsupporting
confidence: 66%
“… 10 , 12 These cells also have a high regenerative effect on surrounding tissue due to the capacity to produce soluble trophic factors. 13 This can promote survival, regeneration, and function of different cells including those of pancreatic islets through paracrine mechanisms driven by MSCs-derived growth factors, cytokines, and chemokines. 9 , 14 The factors secreted by MSCs can also modulate the immune system by inhibition of activation and proliferation of lymphocytes T and B, and dendritic cells, as well as by induction of polarization of macrophages from M1 to M2 state.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have also been shown to improve the insulin secretory response of islets and prolong their survival [29]. The beneficial effects of MSCs in pancreatic islets have been attributed to the secretion of different bioactive paracrine molecules such as growth factors, cytokines, and chemokines [125], as well as their capacity to form extracellular matrix (ECM) as structural support and reservoir for bioactive molecules [123]. However, although the use of MSCs is a very promising approach for application in the clinic, so far, have not led to enough evidence that they are effective in treating diseases [29].…”
Section: Cotransplantation Of Supporting or Immunomodulatory Cellsmentioning
confidence: 99%